2018
DOI: 10.1136/bcr-2018-225643
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of obesity and insulin resistance via ketogenic diet status post Roux-en-Y

Abstract: This is a single case of a 65-year-old American woman who presented with substantial weight gain and insulin resistance (IR) post-Roux-en-Y gastric bypass (RYGB) surgery. Before RYGB, she had reached 340 lbs (155 kg) and a body mass index (BMI) of 56.6 kg/m The surgery resulted in a 70 lbs (32 kg) weight loss, bringing her BMI, per cent total weight loss (%TWL) and per cent excess weight loss (%EWL) to 44.9 kg/m, 20.6% and 36.8%, respectively. Unfortunately, her BMI would return to 53.6 kg/m, nearly her pre-RY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Numerous studies have confirmed the role of KD consumption in weight reduction in obese patients [35][36][37][40][41][42][43]52 ; the current meta-analysis focused on the effect of KD on weight reduction in obese diabetic patients. The results showed the average reduction of body weight was 8.66 kg, waist circumference was 9.17 cm, and BMI was 3.22 kg/m 2 , which were consistent with previous studies in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the role of KD consumption in weight reduction in obese patients [35][36][37][40][41][42][43]52 ; the current meta-analysis focused on the effect of KD on weight reduction in obese diabetic patients. The results showed the average reduction of body weight was 8.66 kg, waist circumference was 9.17 cm, and BMI was 3.22 kg/m 2 , which were consistent with previous studies in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have consistently shown that the KD significantly contributes to weight loss in obese patients. [10,[28][29][30][31][32][33][34][35][36] The reduction in body weight can be attributed to the very low carbohydrate content of the KD, and also to the energy restriction that leads to negative nitrogen balance. Although the control group followed the diabetic diet with energy restriction, the KD with 2 meals per day was superior to the regular diabetic diet at every meal in reducing body weight, body fat, and blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are very few studies examining the significance of KD in reducing insulin resistance in diabetic individuals; the majority of these studies concentrated on the impact on obese people [20]. For example, a controlled clinical investigation examining the impacts of KD consumption in obese individuals who don't have diabetes found that after consuming KD for 6 weeks, patients with insulin resistance in T2DM are more likely to have lipid metabolic disorders than other patient groups [21]. Dyslipidemia causes or worsens insulin resistance because it is lipotoxic to cells.…”
Section: Effect Of Ketogenic Diet On Some Biochemical Parametersmentioning
confidence: 99%